RETINAL VASCULAR CHANGES IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Vasilijevic, Jelena; Laban Lazovic, Marija; Pantelic, Jelica; Kalezic, Tanja; Sofronijevic, Kosana; Popovic, Andjela; Svetel, Marko; Polovina, Snezana; Kovacevic, Igor (Medical Research, 2026)
INTRODUCTION/AIM Chronic obstructive pulmonary disease (COPD) is a progressive and inflammatory disease of the airways that often leads to cardiovascular and microvascular changes. This study aimed to analyze retinal microcirculation in patients with COPD using optical coherence tomography angiography (OCTA)MATERIALS AND METHODS Cross-sectional study. A total of 44 subjects were analyzed, including 28 with COPD and 16 healthy controls. Inclusion criteria were subjects older than 18 years with a confirmed COPD diagnosis based on spirometric parametersRESULTS The statistically significant differences were observed between the groups for the following parameters: deep capillary plexus macular (p = 0.009), parafoveal (p = 0.026), and perifoveal region (p = 0.034). A significant negative correlation was observed between the ratio of residual volume to total lung capacity (RV/TLC) and the vessel density in the macular and perifoveal superficial capillary plexus regions (p
Keywords: optical coherence tomography angiography, chronic obstructive pulmonary disease, vessel density, biomarkers